Estimating dynamic tax revenue elasticities for Germany - Gerrit B. Koester; Christoph Priesmeier (Deutsche Bundesbank, 2012)
We analyse tax revenue elasticities by applying dynamic models to a new disaggregated dataset for Germany, which is adjusted for the effects of tax reforms. We estimate long-run elasticities that are substantially lower than in comparable studies for profit-related taxes and are slightly lower for value-added taxes, whereas the long-run elasticity for wage taxes is close to the consensus estimate in the literature. Additionally, we find that differences between short- and long-run elasticities are particularly important with respect to profit-related taxes. Here we estimate a far lower contemporaneous response to tax base changes than other studies and a dynamic reaction pattern spanning several years, which can be explained, for example, by tax collection lags.
Keywords: H2; H24; H25; E26; 330; Dynamic tax revenue elasticities; Disaggregated analysis; Error correction models